THE PERBANDINGAN SENAM KEGEL 1X SEMINGGU DENGAN 3X SEMINGGU TERHADAP PENURUNAN FREKUENSI BUANG AIR KECIL PADA WANITA DEWASA USIA 50-60 TAHUN DENGAN STRESS URINARY INCONTINENCE - Lestari, Widijati (Majalah Ilmiah Fisioterapi Indonesia, 2013)
Being healthy is a state in which a person can perform daily activities without any disturbance of motion and body function. This situation can be achieved by regular exercises. The presence of disease or injury can reduce the status of one's health and functional ability. One of which is the frequency of urination disorders in adult women who experience stress urinary incontinence at the age of 50-60 years. The objective of the study is to determine the effect of increasing number of frequency of Kegel's exercises to lower the frequency of urination of 50-60 years old women. Forty participants, suspected with stress urinary incontinence, are examined. The examination is taken place at the gymnasium gymnastics Citra Denpasar, Bali. The participants are randomly selected and appointed for treatment schedule of Kegel’s exercises training once a week and three times a week. Frequencies of urination within 24 hours for 4 months of each participant are recorded before and after Kegel's exercises. Samples are tested by non- parametric Wilcoxon test in order to analyze the differences of the frequency of urination which occur before and after training in both groups. Similarly, those are tested by Mann Whitney test in order to reveal the difference amongst groups before and after treatment. The Limit of significance is p equal to 0.05. The result shows that the frequency mean of urination before treatment upon the Kegel’s groups that are undergone the exercises once a week is as many as 10.00 times a day. Meanwhile, the result after training is as many as 9.50 times a day with p value of 0.004 and statistically significant (p <0.05). The mean of frequency of urination after training at the Kegel’s exercises three times a week is as many as 3.50 times a day with p value of 0.000, which is statistically significant. The frequency difference of urination amongst the groups before treatment with p value of 1.000 is statistically not significant, whereas p value amongst the groups after treatment is 0.000, statistically significant. As a conclusion, the regular treatment of Kegel's once and three times a week within four months can lower the frequency of urination. Whilst exercising Kegel’s three times a week is more effective in lowering the frequency of urination compared to that of once a week.
Keywords: Kegel' s exercises, frequency of urination, stress urinary incontinence.